2019
DOI: 10.21613/gorm.2019.903
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Toxoplasma gondii, Rubella and Cytomegalovirus Infection Screening Among Pregnant Women Attending Tertiary University Hospital

Abstract: <p><strong>Objective:</strong> The present study was designed to determine the seroprevalance of Toxoplasma gondii, Rubella, and cytomegalovirus, to investigate the frequency of low and high avidity results among pregnant women and to contribute to the data of our country with the results obtained.</p><p><strong>Study Design:</strong> In the present study, the hospital records of the women who applied to the antenatal outpatient of the Rize Recep Tayyip Erdoğan Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…5 We demonstrated that anti-T. gondii IgG seropositivity ranges between 9.2% and 68% in different regions. 8,10,[16][17][18][19][20] Evaluation of anti-T. gondii IgG in our study showed a seropositivity rate of 18.70% (1745/9322). Toklu found that anti-T. gondii IgG seroprevalence was 18.3%.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…5 We demonstrated that anti-T. gondii IgG seropositivity ranges between 9.2% and 68% in different regions. 8,10,[16][17][18][19][20] Evaluation of anti-T. gondii IgG in our study showed a seropositivity rate of 18.70% (1745/9322). Toklu found that anti-T. gondii IgG seroprevalence was 18.3%.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, considering the socio-economic levels of Ankara, anti-CMV seropositivity was observed less frequently compared to other studies. [16][17][18][19]25 Pradhan 9 and Sen et al 13 found higher anti-CMV IgM seropositivity rates compared to other studies. This may be related to the higher prevalence of infections that are transmitted by droplets in these countries and it may also be related to larger households and worse sanitation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in many countries worldwide, Rubella seropositivity is screened before pregnancy and during the first trimester of pregnancy. Despite effective vaccination programs, Rubella seropositivity has been reported to vary from 71% to 98% in some countries (16). The vaccination against Rubella, which began in 1995 in Turkey, has been continuing since 2006 to include all individuals under 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States it is estimated that 11% of the population 6 years and older have been infected with Toxoplasma (Robert-Gangneux and Dardé, 2012). In Turkey, Rize, Toxoplasma gondii IgM seropositivity was determined as 0.83% and IgG 33.64% in pregnant women (Gurlek and Colak, 2019). If a pregnant woman becomes infected shortly before or during pregnancy, she can transmit the disease to the fetus and it can cause serious complications in the fetus (Dubey, 2016).…”
Section: Introductionmentioning
confidence: 99%